2020
DOI: 10.15421/012042
|View full text |Cite
|
Sign up to set email alerts
|

Features of exogenous development of Trichuris globulosa (Nematoda, Trichuridae)

Abstract: Parasitic nematodes of the genus Trichuris Röderer, 1761 are hematophagous helminths, capable of parasitizing many different hosts including humans. The domestic and wild ruminants are hosts of several Trichuris species, with Trichuris globulosa (Linstow, 1901) one of the most prevalent parasites found in cattle. The exogenous stages of the helminth’s life cycle develop in the outer environment, and their activity and survival depend on the abiotic factors. Thus the aim of the work was to determine the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Тому було проведено вивчення впливу температури на ембріональний розвиток трихурисів овець виду T. ovis, які, згідно з науковими дослідженнями, є доволі поширеним видом на території багатьох країн світу (Yaro et al, 2015;Yevstafieva et al, 2018;Melnychuk et al, 2020). (Yevstafieva et al, 2015;Melnychuk & Berezovsky, 2018;Yevstafieva et al, 2019;Yevstafieva et al, 2020).…”
Section: результати та їх обговоренняunclassified
“…Тому було проведено вивчення впливу температури на ембріональний розвиток трихурисів овець виду T. ovis, які, згідно з науковими дослідженнями, є доволі поширеним видом на території багатьох країн світу (Yaro et al, 2015;Yevstafieva et al, 2018;Melnychuk et al, 2020). (Yevstafieva et al, 2015;Melnychuk & Berezovsky, 2018;Yevstafieva et al, 2019;Yevstafieva et al, 2020).…”
Section: результати та їх обговоренняunclassified
“…Recently, scientists have noted the high viability and resistance to negative effects of eggs of Trichuris nematodes. Thus, the viability of T. skrjabini eggs in laboratory conditions, depending on the temperature, ranged from 75.3% to 80.3%, and that of T. globulosa eggs from 68.0% to 76.3% (Yevstafieva et al, 2020(Yevstafieva et al, , 2023. Also, the authors showed that the eggs of T. suis released by animals into the external environment are more adapted to the conditions of the external environment (survival was 96.6 ± 0.3%) than eggs isolated from the gonads of female nematodes (survival was 89.3 ± 0.3%) (Yevstafieva et al, 2016).…”
Section: Introductionmentioning
confidence: 99%